Development of a manure spreader - Adgidzi, D; Balami, A.A.; Bashir, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2007)
A manure spreader was designed, constructed and evaluated. Cow dung collected from abattoirs was composted and used to test the machine in the field. Bulk density, moisture content, angle of repose and coefficient of friction of the composted dung were determined and found to be 791.9 kgm-3, 44%, 420 and 0.88 respectively. The developed machine was tested in the field using the organic manure and the following parameters were obtained: rate of application of 5.9 tha-1, field capacity of 0.6 hah-1, efficiency of discharge of 86% (when fed with a 75 kg of the manure) and operating width of 1.096 m